PENGARUH PENDAPATAN, BIAYA ADMINISTRASI UMUM DAN AKTIVA TETAP TERHADAP LABA PADA PT. BELILAS PERMAI INDRAGIRI - ANGGA HAPSILA; IVALAINA ASTARINA; PUSPA DEWI; YUDHA REMOFA; HASANAH YASPITA (Fakultas Ekonomi Universitas Islam Indragiri, 2023)
The research was conducted to test and analyze the effect of income, general administration costs and fixed assets on profits at PT. Belilas Permai Indragiri. This study used secondary data, the authors processed the data using the Statistical Package for the Social Sciences (SPSS) application version 24. The results of the study simultaneously income, administration costs and fixed assets affect profit. Partially, income and general administration costs have an effect on profits, while fixed assets have not had a partial effect on profits